Riview : Pentingnya Penyuluhan Kesehatan Untuk Meningkatkan Pengetahuan Ibu Terkait Imunisasi Pada Anak Anak - Siti Farikha; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
According to the Indonesian Health Demographic Survey in 2014 the neonatal mortality rate was up to 19/1000 live births. The infant mortality rate is 32/1000 live births and the under-five mortality rate is 40/1000 live births. According to the results of Riskesdas in 2013 that the coverage of incomplete immunization was 32.1%, complete immunization was 59.2% and 8.7% had never been immunized. Efforts to protect children under five are immunizations. Immunization is an effort to provide immunity to infants and children by introducing vaccines into the body in order to make antibodies that can prevent certain diseases. Several reasons were found that caused infants and toddlers not to get complete immunizations, namely because of the lack of information about the mother's knowledge. Mother's knowledge is very important. For this reason, counseling is the right and good solution in overcoming this. The method used in this journal review is to do a library search using Google Scholar. From the results of several journals, immunization counseling can increase knowledge of mothers